Association between psychiatric disorders and osteoarthritis: a nationwide longitudinal population-based study. Issue 26 (June 2016) - Huang, Shih-Wei; Wang, Wei-Te; Lin, Li-Fong; Liao, Chun-De; Liou, Tsan-Hon; Lin, Hui-Wen
Abstract : Abstract: Although the association between depressive disorders and osteoarthritis (OA) has been studied, the association of other psychiatric disorders with OA remains unclear. Here, we investigated whether psychiatric disorders are risk factors for OA. The data were obtained from the Longitudinal Health Insurance Database 2005 of Taiwan. We collected the ambulatory care claim records of patients who were diagnosed with psychiatric disorders according to the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes between January 1, 2004 and December 31, 2008. The prevalence and adjusted hazard ratios (HRs) of osteoarthritis among patients with psychiatric disorders and the control cohort were estimated. Of 74, 393 patients with psychiatric disorders, 16, 261 developed OA during the 7-year follow-up period. The crude HR for OA was 1.44 (95% confidence interval [CI], 1.39–1.49), which was higher than that of the control cohort. The adjusted HR for OA was 1.42 (95% CI, 1.39–1.42) among patients with psychiatric disorders during the 7-year follow-up period. Further analysis revealed that affective psychoses, neurotic illnesses or personality disorders, alcohol and drug dependence or abuse, and other mental disorders were risk factors for OA. This large-scale longitudinal population-based study revealed that affective psychoses, personality disorders, and alcohol and drug dependence or abuse are risk factors for OA.